Rapidly cross-linked recombinant mussel adhesive protein adhesive as well as preparation and application thereof

Through the design of the rapidly crosslinked recombinant mussel mucin adhesive, the problem of degradation of the performance of wet adhesives in the prior art in humid environments is solved, and rapid and firm bonding and high-humidity bonding are achieved in wet environments. Attached performance.

CN119386250APending Publication Date: 2025-02-07XIAN DENUOHISI MEDICAL TECH CO LTD

Patent Information

Application Number
CN202411592290.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The bonding strength and mechanical properties of existing wet adhesives are significantly weakened in humid environments, and it is difficult to meet the requirements of water-based adhesive repair.

Method used

By changing the product design method of recombinant mussel mucin adhesive, using rapid crosslinking method to reduce the amount of catalyst and increase the crosslinking rate, a adhesive that can quickly and firmly bond under a wet environment was prepared.

Benefits of technology

It achieves rapid and firm bonding in wet environments, improves the wet adhesion performance of the adhesive, and solves the problems of low raw material utilization and long cross-linking time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386250A_ABST
    Figure CN119386250A_ABST
Patent Text Reader

Abstract

The invention discloses a rapidly cross-linked recombinant mussel adhesive protein adhesive as well as preparation and application thereof, and relates to the technical field of biological adhesives. According to the preparation method of the rapidly cross-linked recombinant mussel mucin adhesive, by changing the cross-linking mode of the recombinant mussel mucin, the dosage of the catalyst can be reduced, rapid cross-linking can be realized, and the mechanical property and viscoelasticity of the adhesive can be regulated and controlled according to requirements in the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biological adhesives and relates to a fast cross-linked recombinant mussel adhesive and a preparation method and application thereof. Background Art

[0002] Bioadhesives are medical materials that can seal wounds, stop bleeding quickly, and promote wound healing, and can replace traditional wound suture technology. With the improvement of medical standards, people have an increasing demand for bioadhesives that can be used underwater or under physiological conditions. However, since it is very challenging to achieve adhesion in the presence of water, it is very necessary to produce adhesives that can be used in humid environments. The wet adhesives currently developed show severe swelling in the humid environment of the body, and the bonding strength and mechanical properties are significantly weakened. On the other hand, the water molecules in the interface boundary layer hinder the direct contact between the adhesive and the substrate, resulting in the inability to meet the requirements of water-based adhesive repair. Therefore, wet adhesives with short curing time, strong instantaneous adhesion underwater and high water resistance are still difficult to find.

[0003] In recent years, inspired by mussels, mussel or biomimetic mussel adhesives that strongly adhere to biological tissues in wet environments have attracted widespread attention from scientists. By analyzing the adhesion mechanism of mussel mucin, researchers found that the special proteins secreted by mussels enable them to adhere firmly to the surface even in rough waves because the dopa groups in mussel mucin have the ability to adhere tenaciously to various surfaces under wet conditions. The dopa groups in mussel mucin can interact with the targeted interface through hydrogen bonds, metal ion-dopa coordination bonds, π–π / π-cation / π-z stacking, oxidative cross-linking and electrostatic effects. Therefore, research on the adhesion of mussels in wet environments has received much attention.

[0004] Existing wet adhesives prepared with mussel mucin as the main material mainly improve the bonding strength and mechanical properties by introducing modified groups or compounding with other components to increase cohesion, but the initial synthesis of such adhesives, the proportion adjustment after compounding, the reaction control conditions, and the post-processing steps may make the process cumbersome and complicated. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention changes the design mode of the existing recombinant mussel mucin adhesive product, accelerates the cross-linking rate and reduces the amount of catalyst used, thereby obtaining a fast-cross-linking recombinant mussel mucin adhesive.

[0006] To achieve the above object, the present invention provides a method for preparing a rapidly cross-linked recombinant mussel mucin adhesive, comprising the following steps:

[0007] (1) using freeze-dried unoxidized recombinant mussel mucin as a first component;

[0008] (2) taking another freeze-dried unoxidized recombinant mussel mucin and dissolving it in an alkaline buffer solution containing either persulfate or hydrogen peroxide, mixing well and freeze-drying to obtain oxidized recombinant mussel mucin powder as the second component;

[0009] (3) dry-mixing the first component and the second component to obtain a recombinant mussel mucin mixed powder, adding an acidic buffer solution and mixing evenly to obtain a solution A; wherein the content of the first component in the recombinant mussel mucin mixed powder is 30-80wt%, and the concentration of the recombinant mussel mucin in the solution A is 5-50wt%;

[0010] (4) dissolving the catalyst in the diluent, mixing evenly, and adjusting the pH of the reaction system to a range of 5-9 to obtain a solution B; wherein the catalyst comprises a metal ion compound or a mixture of a metal ion compound and an oxidant, and the metal ion compound is selected from one or more of ferric chloride, zinc chloride, calcium chloride, magnesium sulfate, and copper sulfate; and the concentration of the catalyst in the solution B is 1-20 wt %;

[0011] (5) Mix equal volumes of solution A and solution B to obtain a rapidly cross-linked recombinant mussel mucin adhesive.

[0012] In some other embodiments, in the step (2), the pH of the alkaline buffer solution is 7.0-9.0; and the content of the persulfate or hydrogen peroxide is 0.2-2 wt %.

[0013] Preferably, the alkaline buffer solution is a phosphate buffer solution; and the persulfate is sodium persulfate and / or potassium persulfate.

[0014] In some other embodiments, in the step (2), the specific operation of mixing uniformly is: stirring at a speed of 300-1000 r / min for 30-90 min.

[0015] In some other embodiments, in step (3), the pH of the acidic buffer solution is 5.0-6.8.

[0016] Preferably, the acidic buffer solution is a mixed solution of one or more of a sodium acetate buffer solution, a phosphate buffer solution, and a citrate buffer solution with a content of 0.2-2 wt%.

[0017] In some other embodiments, in step (4), the oxidant is selected from one or more of sodium periodate, ammonium persulfate, perchloric acid, and hydrogen peroxide.

[0018] Preferably, in the catalyst, the mass ratio of the metal ion compound to the oxidant is 1:(0.3-10).

[0019] In some other embodiments, in the step (4), the diluent is selected from one or more of a phosphate buffer solution with a content of 0.2-2 wt %, a physiological saline solution;

[0020] In some other embodiments, in step (4), a pH regulator is used to adjust the pH of the reaction system to a range of 5-9.

[0021] In some other embodiments, steps (3) to (5) of the above preparation method can be performed in a double syringe, as follows:

[0022] (3) dry-mixing the first component and the second component to obtain a recombinant mussel mucin mixed powder, encapsulating the mixed powder in one of the double syringes, adding an acidic buffer through a Luer connector and mixing evenly to obtain a solution A; wherein the content of the first component in the recombinant mussel mucin mixed powder is 30-80wt%, and the concentration of the recombinant mussel mucin in the solution A is 5-50wt%;

[0023] (4) dissolving the catalyst in the diluent, mixing evenly, adjusting the pH of the reaction system to a range of 5-9 to obtain a B solution, and encapsulating the B solution in another syringe of the double syringe through a Luer connector; wherein the catalyst comprises a metal ion compound or a mixture of a metal ion compound and an oxidant, and the metal ion compound is selected from one or more of ferric chloride, zinc chloride, calcium chloride, magnesium sulfate, and copper sulfate; and the content of the catalyst in the B solution is 1-20 wt %;

[0024] (5) Pushing solution A and solution B in the dual syringe to the mixing nozzle to mix equal volumes to obtain a rapidly cross-linked recombinant mussel mucin adhesive.

[0025] The fast cross-linked recombinant mussel mucin adhesive of the present invention is prepared by adopting the above preparation method.

[0026] The method for using the fast cross-linked recombinant mussel mucin adhesive of the present invention is as follows: the prepared fast cross-linked recombinant mussel mucin adhesive is quickly applied to the position to be bonded within 1 minute, and naturally cured for 30 minutes to 60 minutes to achieve firm bonding.

[0027] The above-mentioned fast cross-linked recombinant mussel mucin adhesive of the present invention can be applied to the fields of medicines, medical dressings, implants, hemostatic materials, etc.

[0028] The invention controls the oxidation degree of recombinant mussel mucin, the proportion of unoxidized recombinant mussel mucin in the overall recombinant mussel mucin mixed system, the system pH, the catalyst content and other conditions, so that multiple forms such as DOPA and DOPA-quinone cross-linking structure, DOPA-metal ion coordination bond, and covalent bond formed by DOPA and DOPA-quinone and tissue interface exist in the overall bonding system at the same time, so that the viscoelasticity and cohesion of the final prepared product are effectively enhanced.

[0029] Compared with the prior art, the present invention has the following beneficial technical effects:

[0030] ① The present invention mixes the obtained first component and second component powders in a dry state and then dissolves them in an acidic buffer solution to obtain a pre-gel solution, which is then quickly mixed with a catalyst solution to achieve rapid bonding, so that there are multiple forms of DOPA and DOPA-quinone cross-linking structures, DOPA-metal ion coordination bonds, and covalent bonds between DOPA and DOPA-quinone and tissue interfaces in the system. A large amount of DOPA and DOPA-quinone in the system form covalent bonds with the tissue interface, which can maximize the wet adhesion performance of the adhesive, thereby solving the problems of low raw material utilization, long cross-linking time, etc. caused by directly using unoxidized recombinant mussel mucin for cross-linking in the prior art.

[0031] ② In order to improve the utilization rate of raw materials, in this scheme, the unoxidized recombinant mussel mucin is dissolved in an alkaline buffer solution containing persulfate or hydrogen peroxide, subjected to oxidation treatment and then freeze-dried. This can also avoid to the greatest extent the problem of cross-linking of dopa and newly oxidized dopaquinone present in existing mussel mucin adhesives, thereby reducing the wet adhesion performance of the adhesive.

[0032] ③ In order to achieve rapid cross-linking, the catalyst can be encapsulated in one of the syringes of the double syringe through the Luer connection fitting. When in use, the A solution and the B solution in the double syringe are pushed to the mixing nozzle by the push plate to mix equal volumes, and the catalyst is introduced into the system. The introduction of the catalyst not only accelerates the cross-linking rate between dopa and dopaquinone in the system, and enhances the covalent interaction between dopaquinone and the tissue surface in the system; it also utilizes the chelation of metal ions with dopa groups to form coordination bonds, which accelerates the overall reaction efficiency of the bonding system and further enhances the viscoelasticity of the system, thereby achieving rapid and firm bonding of the product in a wet environment.

[0033] ④ The preparation method of the present invention is easy to operate, low in price, and easy to regulate the mechanical properties and adhesive properties of the adhesive. Moreover, the system is an adhesive body used in a wet environment, which is convenient for clinical use. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.

[0035] Figure 1 It is an operation diagram of the lap-shear tensile bearing strength test in the present invention.

[0036] Figure 2 This is the appearance of the finished products of Example 1, Comparative Example 4, and Comparative Example 8 in the gel time test.

[0037] Figure 3 It is a dynamic frequency scanning diagram of the gel of the adhesive mechanical test of Example 1 of the present invention and Comparative Example 1.

[0038] Figure 4 The cell morphology diagrams are of Example 1, Comparative Example 4, Comparative Example 8, negative control group, and positive control group.

[0039] Figure 5 The graphs show the healing status of the wounds in the experimental group and the blank group on the 1st (1d), 8th (8d), and 14th (14d) days. DETAILED DESCRIPTION

[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0042] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0043] The recombinant mussel mucin used in the following examples and comparative examples is a recombinant mussel mucin rich in DOPA, obtained by bioengineering Escherichia coli fermentation, and provided by Xi'an De Nohais Medical Technology Co., Ltd. For details, reference can be made to the method disclosed in patent document CN116947996A.

[0044] The formulation components and preparation methods of each embodiment and comparative example are as follows.

[0045] Example 1

[0046] Six portions of freeze-dried unoxidized recombinant mussel mucin were used as the first component; four portions of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 7.4) containing 0.5 wt% sodium persulfate, and stirred for 45 min at a speed of 500 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were mixed in a dry state at a mass ratio of 6:4 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and a 1 wt% sodium acetate buffer solution (pH 7.4) was added through a Luer connector. 5.5) and mixed evenly to obtain solution A (recombinant mussel mucin concentration is 30wt%); separately, a mixture of ferric chloride / sodium periodate (mass ratio 1:0.5) is dissolved in a 1wt% phosphate buffer solution and mixed evenly, and the pH of the reaction system is adjusted to 6.8 with a pH regulator to obtain solution B (the mass fraction of the ferric chloride / sodium periodate mixture in the solution is 10wt%), and the solution B is encapsulated in another syringe of the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe are pushed to the mixing nozzle by a push plate to mix equal volumes to obtain a rapidly cross-linked recombinant mussel mucin adhesive.

[0047] Example 2

[0048] 8 parts of freeze-dried unoxidized recombinant mussel mucin were used as the first component; 2 parts of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 9.0) containing 2.0 wt% ammonium persulfate, and stirred for 90 min at a speed of 1000 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were mixed in a dry state at a mass ratio of 8:2 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and a 2 wt% phosphate buffer solution (pH 9.0) was added through a Luer connector. 6.8) Mix well to obtain solution A (recombinant mussel mucin concentration is 50wt%); calcium chloride is dissolved in 2wt% physiological saline solution and mixed well, the pH of the reaction system is adjusted to 9 with a pH regulator to obtain solution B (the mass fraction of calcium chloride in the solution is 20wt%), and the solution B is encapsulated in another syringe of the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe are pushed to the mixing nozzle by a push plate to mix equal volumes to obtain a rapidly cross-linked recombinant mussel mucin adhesive.

[0049] Example 3

[0050] Three portions of freeze-dried unoxidized recombinant mussel mucin were used as the first component; seven portions of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 7.0) containing 0.2 wt% hydrogen peroxide, and stirred for 30 min at a speed of 300 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were mixed in a dry state at a mass ratio of 3:7 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and a 0.2 wt% citrate buffer solution (pH 7.0) was added through a Luer connector. 5.0) are mixed evenly to obtain solution A (the concentration of recombinant mussel mucin is 5wt%); another copper sulfate / ammonium persulfate (mass ratio 1:0.3) mixture is dissolved in 0.2wt% physiological saline solution and mixed evenly, the pH of the reaction system is adjusted to 5 by a pH regulator to obtain solution B (the mass fraction of the copper sulfate / ammonium persulfate mixture in the solution is 1wt%), and the solution B is encapsulated in another syringe in the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe are pushed to the mixing nozzle by a push plate and mixed in equal volumes to obtain a rapidly cross-linked recombinant mussel mucin adhesive.

[0051] Example 4

[0052] Six portions of freeze-dried unoxidized recombinant mussel mucin were used as the first component; four portions of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 7.4) containing 0.5 wt% sodium persulfate, and stirred for 45 min at a speed of 500 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were mixed in a dry state at a mass ratio of 6:4 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and 1 wt% sodium acetate (pH 5.5) and 1 wt% phosphate buffer solution (pH 7.4) were added through a Luer connector. 5.5) Mix well to obtain solution A (recombinant mussel mucin concentration is 30wt%); separately take a mixture of zinc chloride / magnesium sulfate / hydrogen peroxide (mass ratio 1:0.2:0.3) and dissolve it in 1wt% phosphate buffer and 1wt% physiological saline solution and mix well; use a pH regulator to adjust the pH of the reactant to 6.8 to obtain solution B (the mass fraction of the zinc chloride / magnesium sulfate / hydrogen peroxide mixture in the solution is 10wt%); encapsulate solution B in another syringe in the double syringe through a Luer connection fitting; push solution A and solution B in the double syringe to the mixing nozzle through a push plate to mix equal volumes to obtain a rapidly cross-linked recombinant mussel mucin adhesive.

[0053] Comparative Example 1

[0054] Six portions of freeze-dried unoxidized recombinant mussel mucin were used as the first component; four portions of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 7.4) containing 0.5 wt% sodium persulfate, and stirred for 45 min at a speed of 500 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were dry-mixed in a mass ratio of 6:4 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and a 1 wt% sodium acetate buffer solution (pH 7.4) was added through a Luer connector. 5.5) and mixing well to obtain solution A (recombinant mussel mucin concentration is 2.5wt%); separately, a mixture of ferric chloride / sodium periodate (mass ratio is 1:0.5) is dissolved in a 1wt% phosphate buffer solution and mixed well, and the pH of the reaction system is adjusted to 6.8 with a pH regulator to obtain solution B (the mass fraction of the ferric chloride / sodium periodate mixture in the solution is 10wt%), and the solution B is encapsulated in another syringe of the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe are pushed to the mixing nozzle by a push plate and mixed in equal volumes to obtain the adhesive of Comparative Example 1.

[0055] In this comparative example: the mass fraction of recombinant mussel mucin in solution A was adjusted to 2.5 wt %; the rest was the same as in Example 1.

[0056] Comparative Example 2

[0057] Six portions of freeze-dried unoxidized recombinant mussel mucin were used as the first component; four portions of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 7.4) containing 0.5 wt% sodium persulfate, and stirred for 45 min at a speed of 500 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were mixed in a dry state at a mass ratio of 6:4 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and a 1 wt% sodium acetate buffer solution (pH 7.4) was added through a Luer connector. 5.5) and mixing well to obtain solution A (recombinant mussel mucin concentration is 60wt%); separately, a mixture of ferric chloride / sodium periodate (mass ratio 1:0.5) is dissolved in a 1wt% phosphate buffer solution and mixed well, and the pH of the reaction system is adjusted to 6.8 with a pH regulator to obtain solution B (the mass fraction of the ferric chloride / sodium periodate mixture in the solution is 10wt%), and the solution B is encapsulated in another syringe in the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe are pushed to the mixing nozzle by a push plate and mixed in equal volumes to obtain the adhesive of comparative example 2.

[0058] In this comparative example: the mass fraction of recombinant mussel mucin in solution A was adjusted to 60 wt %; the rest was the same as in Example 1.

[0059] Comparative Example 3

[0060] Six portions of freeze-dried unoxidized recombinant mussel mucin were used as the first component; four portions of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 7.4) containing 0.5 wt% sodium persulfate, and stirred for 45 min at a speed of 500 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were mixed in a dry state at a mass ratio of 6:4 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and a 1 wt% sodium acetate buffer solution (pH 7.4) was added through a Luer connector. 5.5) and mixing well to obtain solution A (recombinant mussel mucin concentration is 30wt%); separately taking a mixture of ferric chloride / sodium periodate (1:0.5) and dissolving it in a 1wt% phosphate buffer solution and mixing well, then adding a pH regulator to adjust the pH of the reaction system to 6.8 to obtain solution B (the mass fraction of the ferric chloride / sodium periodate mixture in the solution is 0.1wt%), and encapsulating solution B in another syringe of the double syringe through a Luer connection fitting; pushing solution A and solution B in the double syringe to a mixing nozzle by a push plate and mixing them in equal volumes to obtain the adhesive of comparative example 3.

[0061] In this comparative example: the mass fraction of the ferric chloride / sodium periodate mixture in solution B was adjusted to 0.1 wt %; the rest was the same as in Example 1.

[0062] Comparative Example 4

[0063] Six portions of freeze-dried unoxidized recombinant mussel mucin were used as the first component; four portions of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 7.4) containing 0.5 wt% sodium persulfate, and stirred for 45 min at a speed of 500 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were mixed in a dry state at a mass ratio of 6:4 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and a 1 wt% sodium acetate buffer solution (pH 7.4) was added through a Luer connector. 5.5) and mixing well to obtain solution A (recombinant mussel mucin concentration is 30wt%); separately, a mixture of ferric chloride / sodium periodate (mass ratio 1:0.5) is dissolved in a 1wt% phosphate buffer solution and mixed well, and then a pH regulator is added to adjust the pH of the reaction system to 6.8 to obtain solution B (the mass fraction of the ferric chloride / sodium periodate mixture in the solution is 30wt%), and the solution B is encapsulated in another syringe in the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe are pushed to the mixing nozzle by a push plate and mixed in equal volumes to obtain the adhesive of comparative example 4.

[0064] In this comparative example: the mass fraction of the ferric chloride / sodium periodate mixture in solution B is adjusted to 30 wt %; the rest is the same as in Example 1.

[0065] Comparative Example 5

[0066] Two portions of freeze-dried unoxidized recombinant mussel mucin were used as the first component; 8 portions of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 7.4) containing 0.5 wt% sodium persulfate, and stirred for 45 min at a speed of 500 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were mixed in a dry state at a mass ratio of 2:8 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and a 1 wt% sodium acetate buffer solution (pH 7.4) was added through a Luer connector. 5.5) and mixed evenly to obtain solution A (recombinant mussel mucin concentration is 30wt%); separately, a mixture of ferric chloride / sodium periodate (mass ratio 1:0.5) is dissolved in a 1wt% phosphate buffer solution and mixed evenly, and then a pH regulator is added to adjust the pH of the reaction system to 6.8 to obtain solution B (the mass fraction of the ferric chloride / sodium periodate mixture in the solution is 10wt%), and the solution B is encapsulated in another syringe in the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe are pushed to the mixing nozzle by a push plate and mixed in equal volumes to obtain the adhesive of comparative example 5.

[0067] In this comparative example: the mass ratio of the first component to the second component is adjusted to 2:8; the rest is the same as Example 1.

[0068] Comparative Example 6

[0069] 9 parts of freeze-dried unoxidized recombinant mussel mucin were used as the first component; 1 part of freeze-dried unoxidized recombinant mussel mucin was dissolved in a phosphate buffer solution (pH 7.4) containing 0.5 wt% sodium persulfate, and stirred for 45 min at a speed of 500 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were mixed in a dry state at a mass ratio of 9:1 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and a 1 wt% sodium acetate buffer solution (pH 7.4) was added through a Luer connector. 5.5) and mixed evenly to obtain solution A (recombinant mussel mucin concentration is 30wt%); separately, a mixture of ferric chloride / sodium periodate (mass ratio 1:0.5) is dissolved in a 1wt% phosphate buffer solution and mixed evenly, and then a pH regulator is added to adjust the pH of the reaction system to 6.8 to obtain solution B (the mass fraction of the ferric chloride / sodium periodate mixture in the solution is 10wt%), and the solution B is encapsulated in another syringe in the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe are pushed to the mixing nozzle by a push plate and mixed in equal volumes to obtain the adhesive of Comparative Example 6.

[0070] In this comparative example: the mass ratio of the first component to the second component is adjusted to 9:1; the rest is the same as Example 1.

[0071] Comparative Example 7

[0072] Six portions of freeze-dried unoxidized recombinant mussel mucin were used as the first component; four portions of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 7.4) containing 0.1 wt% sodium persulfate, and stirred for 45 min at a speed of 500 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were mixed in a dry state at a mass ratio of 6:4 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and a 1 wt% sodium acetate buffer solution (pH 7.4) was added through a Luer connector. 5.5) and mixed evenly to obtain solution A (recombinant mussel mucin concentration is 30wt%); separately, a mixture of ferric chloride / sodium periodate (mass ratio 1:0.5) is dissolved in a 1wt% phosphate buffer solution and mixed evenly, and then a pH regulator is added to adjust the pH of the reaction system to 6.8 to obtain solution B (the mass fraction of the ferric chloride / sodium periodate mixture in the solution is 10wt%), and the solution B is encapsulated in another syringe in the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe are pushed to the mixing nozzle by a push plate and mixed in equal volumes to obtain the adhesive of Comparative Example 7.

[0073] In this comparative example: the mass fraction of the phosphate buffer solution containing sodium persulfate is adjusted to 0.1 wt %; the rest is the same as Example 1.

[0074] Comparative Example 8

[0075] Six portions of freeze-dried unoxidized recombinant mussel mucin were used as the first component; four portions of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 7.4) containing 2.5 wt% sodium persulfate, and stirred for 45 min at a speed of 500 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying as the second component; the first component and the second component were mixed in a dry state at a mass ratio of 6:4 to obtain a recombinant mussel mucin mixed powder, which was then encapsulated in one of the syringes of a double syringe, and a 1 wt% sodium acetate buffer solution (pH 7.4) was added through a Luer connector. 5.5) and mixed evenly to obtain solution A (recombinant mussel mucin concentration is 30wt%); separately, a mixture of ferric chloride / sodium periodate (mass ratio 1:0.5) is dissolved in a 1wt% phosphate buffer solution and mixed evenly, and then a pH regulator is added to adjust the pH of the reaction system to 6.8 to obtain solution B (the mass fraction of the ferric chloride / sodium periodate mixture in the solution is 10wt%), and the solution B is encapsulated in another syringe in the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe are pushed to the mixing nozzle by a push plate and mixed in equal volumes to obtain the adhesive of comparative example 8.

[0076] In this comparative example: the mass fraction of the phosphate buffer solution containing sodium persulfate is adjusted to 2.5wt%; the rest is the same as Example 1.

[0077] Comparative Example 9

[0078] 10 portions of freeze-dried unoxidized recombinant mussel mucin powder were encapsulated in one of the syringes of the double syringe, and 1 wt% sodium acetate buffer solution (pH 5.5) was added through a Luer connection fitting and mixed evenly to obtain a solution A (the concentration of recombinant mussel mucin was 30 wt%); another mixture of ferric chloride / sodium periodate (mass ratio 1:0.5) was dissolved in a 1 wt% phosphate buffer solution and mixed evenly, and then a pH regulator was added to adjust the pH of the reaction system to 6.8 to obtain a solution B (the mass fraction of the ferric chloride / sodium periodate mixture in the solution was 10 wt%), and the solution B was encapsulated in the other syringe of the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe were pushed to the mixing nozzle by a push plate and mixed in equal volumes to obtain the adhesive of Comparative Example 9.

[0079] In this comparative example: solution A contains only the first component and no second component; the rest is the same as in Example 1.

[0080] Comparative Example 10

[0081] 10 portions of freeze-dried unoxidized recombinant mussel mucin were dissolved in a phosphate buffer solution (pH 7.4) containing 2.5 wt% sodium persulfate, and stirred for 45 min at a speed of 500 r / min in a dry environment until the mixture was uniformly mixed, and oxidized recombinant mussel mucin powder was prepared by freeze drying; the obtained recombinant mussel mucin mixed powder was then encapsulated in one of the syringes of a double syringe, and a 1 wt% sodium acetate buffer solution (pH 7.4) was added through a Luer connector. 5.5) and mixed evenly to obtain solution A (recombinant mussel mucin concentration is 30wt%); separately, a mixture of ferric chloride / sodium periodate (mass ratio 1:0.5) is dissolved in a 1wt% phosphate buffer solution and mixed evenly, and then a pH regulator is added to adjust the pH of the reaction system to 6.8 to obtain solution B (the mass fraction of the ferric chloride / sodium periodate mixture in the solution is 10wt%), and the solution B is encapsulated in another syringe in the double syringe through a Luer connection fitting; the solution A and the solution B in the double syringe are pushed to the mixing nozzle by a push plate and mixed in equal volumes to obtain the adhesive of Comparative Example 10.

[0082] In this comparative example: solution A contains only the second component but not the first component; the rest is the same as in Example 1.

[0083] The following tests were performed on the adhesives prepared in Examples 1-4 and Comparative Examples 1-10.

[0084] 1. Gel time test

[0085] Test method: The adhesive prepared in Examples 1-4 and Comparative Examples 1-10 was quickly dripped onto a 5 cm × 10 cm rectangular glass within 1 minute. After a period of time, the glass was tilted to 80° with the horizontal plane, and the appearance and sliding of the finished product were observed. The greater the sliding distance, the worse the adhesion effect. The better the adhesion effect was when there was no sliding for 30 seconds. The time point of the change process from pre-gel to gel was then recorded, and the corresponding time record was the gel time.

[0086] 2. Lap-shear tensile bearing strength test

[0087] Test method: According to "YY / T 0729.2-2009 Tissue Adhesive Bonding Performance Test Method Part 1: Lap-Shear Tensile Strength". The specific operation is as follows:

[0088] The adhesives prepared in Examples 1-4 and Comparative Examples 1-10 were rapidly dripped onto fresh pigskin cut to the size specified in YY / T0729.2-2009 within 1 minute, and then a 100-200 g weight was applied to press the bonding parts together with a force of 1 to 2 N until the curing was complete. Figure 1 Then, the sample strip is placed in the fixture of the testing machine, with the force direction being the long axis direction of the sample, and the crosshead is used to load the sample at a speed of 10 mm / min until it is destroyed, and the load at the time of destruction (i.e., tensile strength) is recorded.

[0089] The test results of the adhesives prepared in Examples 1-4 are shown in Table 1.

[0090] Table 1 Test results of adhesives of Examples 1-4

[0091] Test items / results Example 1 Example 2 Example 3 Example 4 Appearance Reddish brown brown Blue Purple Light Brown Gel time min 30±2 45±3 48±3 32±2 Sliding situation No Slide No Slide No Slide No Slide Tensile strength(MPa) 0.111±0.002 0.133±0.005 0.116±0.003 0.111±0.003

[0092] The test results of the adhesives prepared in Comparative Examples 1-8 are shown in Table 2.

[0093] Table 2 Test results of adhesives of comparative examples 1-8

[0094]

[0095] The appearance of the finished adhesives of Example 1, Comparative Example 4 and Comparative Example 8 is as follows Figure 2 shown.

[0096] The test results of the adhesives prepared in Comparative Examples 9 and 10 are shown in Table 3.

[0097] Table 3 Test results of adhesives of comparative examples 9-10

[0098] Test items / results Comparative Example 9 Comparative Example 10 Appearance Light Brown black Gel time min 179±2 52±2 Sliding situation No Slide Slide 1cm Tensile strength(MPa) 0.05±0.005 0.02±0.002

[0099] As shown in Tables 1 to 3, the performance of Comparative Examples 1 to 10 is compared with that of Example 1. The above results show that:

[0100] In Comparative Example 1, when the concentration of recombinant mussel mucin in solution A is too low, it is difficult for the system to achieve fast and firm adhesion through self-polymerization and cross-linking and metal chelation / oxidation due to the low content of unoxidized dopa and oxidized dopaquinone in the system. Therefore, the appearance finally presents a light brown color, the gel time is not shortened, and the sliding condition and tensile strength show that the adhesion performance of the finished product is poor compared with that of Example 1.

[0101] In comparative example 2, when the concentration of recombinant mussel mucin in solution A is 60 wt%, after the catalyst is added to the reaction system, the system has a large amount of dopaquinone, which causes the finished product to appear black due to over-oxidation. Although the gel time is shortened, over-oxidation causes the tensile strength of the final product to be far from that of Example 1, resulting in poor adhesion.

[0102] In comparative example 3, when the catalyst concentration in solution B is too low, a small amount of catalyst causes a portion of the recombinant mussel mucin to form an adhesive through metal chelation / oxidation, while the remaining recombinant mussel mucin needs to form system cohesion through a natural oxidation process. Therefore, the preparation time of the adhesive is greatly increased, and the light brown appearance of the finished product indicates that DOPA is not well oxidized and participates in the cross-linking reaction during the process, so the adhesion performance is poor compared with that in Example 1.

[0103] In comparative example 4, when the catalyst concentration in solution B is too high, the excess catalyst replaces the natural oxidation process to cause a large amount of mussel mucin to be over-oxidized, and the remaining dopaquinone quickly forms a metal chelate with the metal ions, which results in the unoxidized dopa not participating well in the cohesive cross-linking reaction. Therefore, although the curing time is shortened, a black product with over-oxidation and low adhesion is finally formed.

[0104] In comparative example 5, when the mass ratio of the first component to the second component is 2:8, due to the excess of dopaquinone in the reaction system, dopaquinone will agglomerate in advance before the addition of the catalyst, resulting in the inability of dopa and dopaquinone to cross-link and cohere well. After the addition of the catalyst, the recombinant mussel mucin will be over-oxidized, resulting in the blackening of the finished product. Therefore, although it does not take a long time to gel, the sliding condition and tensile strength show that the adhesion performance is significantly poor.

[0105] In comparative example 6, when the mass ratio of the first component to the second component is 9:1, due to the excess of DOPA in the reaction system, a portion of the DOPA in the reaction system will be gradually oxidized into DOPAquinone under the action of the catalyst, and then gradually form an adhesive. However, this undoubtedly increases the time of the final product, and rapid crosslinking cannot be achieved. The adhesion performance is also affected and reduced.

[0106] In comparative example 7, when the concentration of sodium persulfate is too low, only a small amount of DOPA in the reaction system will be oxidized into DOPAquinone, and the remaining DOPA will be gradually oxidized into DOPAquinone under the action of the catalyst, which results in a part of the catalyst that promotes cross-linking being consumed, and the remaining recombinant mussel mucin needs to form system cohesion through a natural oxidation process, thereby increasing the time to form the final product, and failing to achieve rapid cross-linking. The finished product also appears light brown in color because the cross-linking reaction does not occur well during the process, and the adhesion performance is also affected and reduced.

[0107] In Comparative Example 8, when the concentration of sodium persulfate is too high, the over-oxidation self-aggregation of DOPA in the second component of the reaction system leads to agglomeration, and it cannot be fully cross-linked with the unoxidized DOPA in the first component in the subsequent reaction. Therefore, the final product is light brown, the gel time is not shortened, and the adhesion performance is also poor.

[0108] In comparative example 9, when solution A contains only the first component but no second component, since there is only a large amount of DOPA in the reaction system, DOPA in the reaction system will be gradually oxidized into DOPAQUINONE under the action of the catalyst, and the generated DOPAQUINONE will preferentially react with DOPA, resulting in only a small portion of DOPAQUINONE being able to combine with the tissue interface, so that the wet adhesion performance and gelation time of the final product are affected.

[0109] In comparative example 10, when solution A contains only the second component but not the first component, due to the excess of dopaquinone in the reaction system, dopaquinone will aggregate in advance before the addition of the catalyst, resulting in the inability of dopa and dopaquinone to cross-link and cohere well. After the addition of the catalyst, the recombinant mussel mucin will be over-oxidized, resulting in the blackening of the finished product. Therefore, although it does not take a long time to gel, the sliding condition and tensile strength show that the adhesion performance is significantly poor.

[0110] In summary, according to the embodiments 1-4 of the present invention, a fast cross-linking adhesive can be prepared. Comparative Examples 1-8 show that the concentration of solution A should be controlled within 5-50wt%, and the mass ratio of the first component to the second component should be controlled within 3:7-8:2, the concentration of solution B should be controlled within 1-20wt%, and the mass fraction of the phosphate buffer solution containing sodium persulfate should be controlled within 0.2-2wt%, which can greatly shorten the final gelation time, accelerate the gelation process, and maximize the tensile strength. Comparative Examples 9 and 10 illustrate that in the fast bonding system, the first component and the second component are indispensable. When the second component is missing, there are only dopa groups in the bonding system, which not only increases the gelation time of the adhesive, but also most of the oxidized dopaquinones will cross-link with the unoxidized dopa groups, thereby reducing the adhesion of the product; and when the first component is missing, there are a large amount of dopaquinones in the bonding system. Although the gelation time is shortened, dopaquinones will be over-oxidized under the action of the catalyst, resulting in poor mechanical strength and adhesion of the product. In addition, in the lap-shear tensile bearing strength test, the dopa group can form covalent bonds with the nucleophilic groups on the surface of pig skin tissue, such as -NH2, -SH, -OH and -COOH groups, which also increases the tensile strength; and dopaquinone can form hydrogen bonds with unoxidized dopa groups and form covalent bonds with -NH2 and -SH on the surface of pig skin tissue. These synergistic effects further strengthen the gel network, establish long-term strong adhesion, and ultimately affect the adhesion performance of the finished product.

[0111] Furthermore, mechanical tests were performed on the adhesives of Example 1 and Comparative Example 1. Figure 3 The strain angle of the adhesive of Example 1 and Comparative Example 1 is 0.1 to 100 rad s -1 Gel dynamic frequency scanning diagram. Within the tested frequency range, the storage modulus (G′) of the finished adhesive of Example 1 is much larger than the loss modulus (G″), which indicates that the adhesive prepared in Example 1 has better stability in liquid-solid state transition (solid-state response of gel) and mechanical strength after gelation. The storage modulus (G′) of Comparative Example 1 is close to the loss modulus (G″), which indicates that the viscoelasticity and cohesion of the adhesive of Comparative Example 1 after gelation are worse than those of Example 1.

[0112] 3. Cytotoxicity evaluation

[0113] First, L929 fibroblasts were seeded in 96-well plates at a cell density of 2.5 × 10 5 Cells / well were cultured in MEM medium containing antibiotics and 10% serum at 37°C and 5% CO2 for 24 h. Negative and positive control groups were set up.

[0114] Then the original culture medium was discarded, culture medium was added to the negative control group, 10% concentration of dimethyl sulfoxide was added to the positive control group, and the experimental group was the adhesive of Examples 1-4 and Comparative Examples 1-10. The extract of each sample in the experimental group was added to the culture plate with cells, and the culture was continued for 24 hours. Then the cell fluid in the wells was aspirated, 100 μL of culture medium and 10 μL of MTT solution were added to each well, and the incubation and culture were continued for 4 hours.

[0115] After the incubation, discard the liquid in the well, add 150 μL of dimethyl sulfoxide, place on an oscillator for 10 minutes, and use an ELISA reader to detect the absorbance of each sample at 570 nm. Calculate the cell proliferation rate using the following formula:

[0116] Cell proliferation rate = (experimental group - negative control group) / negative control group × 100%.

[0117] The cell proliferation rate of each group was calculated and the results are shown in Table 4.

[0118] Table 4 Cell proliferation rate in each group

[0119]

[0120] The cell morphology of each group was observed under an inverted microscope. The cell morphology of Example 1, Comparative Example 4, Comparative Example 8, negative control group, and positive control group was as follows: Figure 4 shown.

[0121] The results show that the cell proliferation rates of Example 1, Comparative Example 4, Comparative Example 8, negative control group, and positive control group are 101%, 56%, 62%, 98%, and 23%, respectively; the cell morphology of the negative control group is similar to that of Example 1, with no cell lysis and no decrease in cell proliferation, while there are cell lysis and decrease in cell proliferation in Comparative Example 4 and Comparative Example 8. This is because the catalyst concentration in the B solution of Comparative Example 4 is too high, and the excess catalyst in the finished product makes the cell survival rate low, thereby affecting cell proliferation; when the concentration of sodium persulfate in Comparative Example 8 is too high, the excess oxidant changes or dissolves the cell morphology, thereby affecting cell proliferation. Other Examples 2-4, Comparative Examples 1-3, 5-7, 9, and 10 are the same as Example 1, with cell proliferation rates between 98-101%, and cell morphologies are similar to those of Example 1. Therefore, based on the comprehensive cell proliferation rate and cell morphology, it can be determined that the adhesive prepared by the present invention has no cytotoxicity, indicating that it has high biological safety.

[0122] 4. Skin injury healing experiment

[0123] Test method: 4 hours before the test, remove 4×6 cm of hair on both sides of the spine of healthy SD rats to use as the test and observation site. After disinfecting the test site with povidone iodine, use a surgical blade to cause a 2 cm long injury to the entire layer of the skin. Apply the adhesive prepared in Examples 1-4 and Comparative Examples 1-10 to the test area of ​​2.5×0.5 cm in the middle and surrounding of the injury within 1 minute and wait for complete gelation. Record the wound healing time. The results are shown in Table 5.

[0124] Table 5 Wound healing time

[0125]

[0126] The results in Table 5 show that the adhesive prepared according to the preparation method of the present invention can effectively promote wound healing.

[0127] In the skin injury healing experiment, Example 1 was also used as an example as an experimental group, and compared with a blank group (without adhesive, healing under normal conditions), and the wound healing conditions were recorded for 14 days. The healing conditions of the wounds in the experimental group and the blank group on the 1st (1d), 8th (8d), and 14th (14d) days were as follows: Figure 5 On the first day, the blank group was in an open state, while the wound of the experimental group was closed; on the eighth day, the wound of the blank group healed poorly, while the wound of the experimental group had no open wound, the wound was smooth, with new epidermal tissue, and no signs of inflammation or infection; on the 14th day, the wound of the blank group still had an incision mark, while the wound of the experimental group was completely healed, showing the ability of the adhesive in wound repair and skin regeneration.

[0128] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a rapidly cross-linked recombinant mussel mucin adhesive, characterized in that: The following steps are involved: (1) using freeze-dried unoxidized recombinant mussel mucin as a first component; (2) taking another freeze-dried unoxidized recombinant mussel mucin and dissolving it in an alkaline buffer solution containing either persulfate or hydrogen peroxide, mixing well and freeze-drying to obtain oxidized recombinant mussel mucin powder as the second component; (3) dry-mixing the first component and the second component to obtain a recombinant mussel mucin mixed powder, adding an acidic buffer solution and mixing evenly to obtain a solution A; wherein the content of the first component in the recombinant mussel mucin mixed powder is 30-80wt%, and the concentration of the recombinant mussel mucin in the solution A is 5-50wt%; (4) dissolving the catalyst in the diluent, mixing evenly, and adjusting the pH of the reaction system to a range of 5.0-9.0 to obtain a solution B; wherein the catalyst comprises a metal ion compound or a mixture of a metal ion compound and an oxidant, and the metal ion compound is selected from one or more of ferric chloride, zinc chloride, calcium chloride, magnesium sulfate, and copper sulfate; and the concentration of the catalyst in the solution B is 1-20 wt %; (5) Mix equal volumes of solution A and solution B to obtain a rapidly cross-linked recombinant mussel mucin adhesive.

2. The method for preparing the rapidly cross-linked recombinant mussel mucin adhesive according to claim 1, characterized in that: In the step (2), the pH of the alkaline buffer solution is 7.0-9.0; the content of the persulfate or hydrogen peroxide is 0.2-2 wt%.

3. The method for preparing the rapidly cross-linked recombinant mussel mucin adhesive according to claim 2, characterized in that: The alkaline buffer solution is a phosphate buffer solution; the persulfate is sodium persulfate and / or potassium persulfate.

4. The method for preparing the rapidly cross-linked recombinant mussel mucin adhesive according to claim 3, characterized in that: In the step (2), the specific operation of mixing uniformly is: stirring at a speed of 300-1000 r / min for 30-90 min.

5. The method for preparing the rapidly cross-linked recombinant mussel mucin adhesive according to claim 1, characterized in that: In the step (3), the pH of the acidic buffer solution is 5.0-6.

8.

6. The method for preparing the rapidly cross-linked recombinant mussel mucin adhesive according to claim 5, characterized in that: The acidic buffer solution is a mixed solution of one or more of a sodium acetate buffer solution, a phosphate buffer solution and a citrate buffer solution with a content of 0.2-2 wt%.

7. The method for preparing the rapidly cross-linked recombinant mussel mucin adhesive according to claim 1, characterized in that: In the step (4), the oxidant is selected from one or more of sodium periodate, ammonium persulfate, perchloric acid, and hydrogen peroxide.

8. The method for preparing the rapidly cross-linked recombinant mussel mucin adhesive according to claim 1, characterized in that: In the catalyst, the mass ratio of the metal ion compound to the oxidant is 1:(0.3-10).

9. The method for preparing the rapidly cross-linked recombinant mussel mucin adhesive according to claim 1, characterized in that: In the step (4), the diluent is selected from one or more of a phosphate buffer solution with a content of 0.2-2wt% and a physiological saline solution.

10. A rapidly cross-linked recombinant mussel mucin adhesive, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for producing recombinant mussel mucin rich in dopa

    CN116947996A

Cited By

  • Biological sustained-release stent as well as preparation method and application thereof

    CN121130173A